Trends in the Use of Artificial Intelligence in Science Education: Bibliometric & Biblioshiny Analysis (1975-2024) - Ayuni, Rizki Tika; Jaedun, Amat; Zafrullah, Zafrullah; Ramadhani, Atika Miftah (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to look at research trends in the Scopus database regarding the study of Artificial Intelligence in Science Education. Using the PRISMA method, researchers selected and determined 146 documents that were ready to be analyzed using bibliometric and biblioshiny methods with the help of the R program and Vosviewer. From the results of the analysis carried out, it was concluded that research on Artificial Intelligence in Science Education in the Scopus Database started from 1975 to 2024, with an 8-fold increase in the number of publications, and 13 times the number of citations in the last 7 years. China was the country with the highest contribution to this research, showing 17(11.64%) publications and 418(13.65%) citations. "BMC Medical Education" is the most productive source with an h-index of 4. Jose Carpio Cañada from Universidad de Huelva in Spain is the most productive author with an h-index of 2. Y. K. Dwivedi et al., (2021) with 1159(37.85%) citations is the source with highest citation. There are 58 keywords divided into 9 clusters, with the keywords "Digital Technologies", "ChatGPT", and "Systems Thinking" being the main recommendations in the field of artificial intelligence in science education